The Effectiveness of Using the Bogor Traffic Info Application in Handling Traffic Accidents to Minimize Accidents in the Jurisdiction of the Bogor City Police Department - Baskara, Novaldy Dewanda (Advances in Police Science Research Journal, 2024)
This research is motivated by the emergence of problems that often occur in the city of Bogor so that the Bogor City Police Traffic Unit launched an innovation in the form of using the Bogor Traffic Info application in providing excellent service to the community, especially in handling traffic accidents that occur in Bogor City. But until February 2020 the number of Bogor Traffic Info application users is still relatively small, so it is considered not in accordance with the purpose of the innovation. Therefore, a study was conducted aimed at finding out the use of the Bogor Traffic Info application, the factors that influence it, and optimizing its use socialization. This research was conducted with a qualitative approach, using field research methods, research locations in Bogor City Polresta, data sources were divided into two, namely primary data sources and secondary data sources as well as data collection techniques with interviews, observations, and document reviews, data validation namely data source validation , technical data validation and time data validation. The results of the study found that the use of the Bogor Traffic Info application has not yet met the standards. Supporting factors can be divided into two factors, namely internal organization and external organization. For internal organization, there are leadership policies, good work culture and routine socialization. While for external organizations, there are high expectations from the public regarding public service efforts. The inhibiting factors are also divided into two factors namely internal organization and external organization. For internal organizations there are two factors namely, human resource factors, there is no financial support from the Bogor City Polresta and there is no Reward and Punishment for members. Externally, the organization’s level of knowledge and community activeness is an obstacle to the research results. Based on the results of the study, the authors suggest budgeting in the form of maintenance and regular maintenance related to the application, working with local media and electronic media and local radio, expanding application users from Android to iOS, routine outreach efforts in the form of car free day, Bogor city holidays. as well as Bogor Police events and take advantage of work units to help socialize the Bogor Traffic Info application in every activity.